Silent Uterine Rupture with the Use of Misoprostol for Second Trimester Termination of Pregnancy : A Case Report - Martin Cuellar Torriente (Obstetrics and Gynecology International)
Uterine rupture is an uncommon, but a life-threatening, complication following second trimester medical termination of pregnancy (TOP). The reported cases have been in both the scarred and unscarred uterus (Rajesh et al. 2002, Drey et al. 2006, and Dickinson). A 27-year-old with two previous deliveries, no previous caesarean section, no history of induced abortions, and no gynaecological operations. She presented with amenorrhoea, and according to her last normal menstruation, she was 10 weeks and 5 days. Ultrasound was done, and it reported 16 weeks and 5 days. She asked for TOP. According to the clinic's protocol, misoprostol 800 mcg (4 tabs) were given to be used vaginally as a loading dose and another three to be taken orally after that. In the following day when she attended the clinic for follow up, a manual vacuum aspiration (MVA). A manual vacuum aspiration was indicated as an incomplete abortion. During the procedure, a uterine rupture was found in the uterine lower segment. A laparotomy was done and a lineal uterine rupture was found and sutured. The patient had a good postoperative recovery and was discharged from hospital after four days. The clinician dealing with second trimester terminations should be aware of the possibility of having a uterine rupture, especially in patients with a uterine scar in order to make an early diagnosis.